2004
DOI: 10.1073/pnas.0305974101
|View full text |Cite
|
Sign up to set email alerts
|

GABA-mediated giant depolarizing potentials as coincidence detectors for enhancing synaptic efficacy in the developing hippocampus

Abstract: Spontaneously occurring neuronal oscillations constitute a hallmark of developmental networks. They have been observed in the retina, neocortex, hippocampus, thalamus, and spinal cord. In the immature hippocampus, the so-called ''giant depolarizing potentials'' (GDPs) are network-driven synaptic events generated by ␥-aminobutyric acid (GABA), which at this stage is depolarizing and excitatory. We have tested the hypothesis that during the first postnatal week, GDP-associated calcium signals may alter the prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
171
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(185 citation statements)
references
References 50 publications
8
171
1
Order By: Relevance
“…In agreement with a previous study (13), we found that with this delay the pairing procedure failed to induce synaptic potentiation. Before and after pairing, the amplitude of the evoked responses was not significantly different (6.4 Ϯ 1.1 and 4.4 Ϯ 0.9 pA, respectively; P Ͼ 0.5).…”
supporting
confidence: 82%
See 3 more Smart Citations
“…In agreement with a previous study (13), we found that with this delay the pairing procedure failed to induce synaptic potentiation. Before and after pairing, the amplitude of the evoked responses was not significantly different (6.4 Ϯ 1.1 and 4.4 Ϯ 0.9 pA, respectively; P Ͼ 0.5).…”
supporting
confidence: 82%
“…Our findings suggest that ''pairing'' persistently enhances synaptic efficacy at these synapses, an effect that depends on the rise of calcium in the postsynaptic cell. In addition, compared with our previous work (13), in the present study, we identified the intracellular signaling pathway mediating pairinginduced potentiation, which involves the activation of BDNF and the ERK pathway.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…This may be partially attributable to the depolarizing and excitatory action of GABA (Cherubini et al, 1991), which produces giant depolarizing potentials (GDPs) (Ben-Ari et al, 1989; Sipila et al, 2005). GDPs ensure calcium entry through NMDA and voltage-dependent calcium channels (Garaschuck et al, 1998) and act as coincidence detectors and thereby persistently enhance synaptic activity at MF-CA3 synapses (Kasyanov et al, 2004).…”
Section: Introductionmentioning
confidence: 99%